1997
DOI: 10.3109/17518429709167363
|View full text |Cite
|
Sign up to set email alerts
|

Neurological rehabilitation in children and adolescents

Abstract: We report about 38 patients aged between 1 and 19 years (36.8% female, 63.2% male; mean age 7.8 years) admitted as inpatients for further neurorehabilitation mostly 4 weeks after severe acquired brain injury (ABI) of different aetiology. Of the patients, 73.7% were in a state of minimal responsiveness (vigilance score < 7 WVS) on admission. We evaluate the course of rehabilitation and the outcome 6 months after the end of the inpatient-period. The average stay of 15.5 weeks is strikingly low. The average inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Sensory CIPN symptoms in patients treated with taxanes often emerge in a stocking and glove pattern. 20 , 21 To assess sensory changes, cold sensibility was measured delivering stimuli with an ice cold Tip‐Therm and pinprick sensibility was measured delivering stimuli with a BD™ 18 G Blunt Fill Needle. Stimuli were given every 3 cm from the cubital fossa to the top of the third digit and from the patella to the top of the first (big) toe on the left and right side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory CIPN symptoms in patients treated with taxanes often emerge in a stocking and glove pattern. 20 , 21 To assess sensory changes, cold sensibility was measured delivering stimuli with an ice cold Tip‐Therm and pinprick sensibility was measured delivering stimuli with a BD™ 18 G Blunt Fill Needle. Stimuli were given every 3 cm from the cubital fossa to the top of the third digit and from the patella to the top of the first (big) toe on the left and right side.…”
Section: Methodsmentioning
confidence: 99%
“…Sensory CIPN symptoms in patients treated with taxanes often emerge in a stocking and glove pattern 20,21 . To assess sensory changes, cold sensibility was measured delivering stimuli with an ice cold Tip‐Therm and pinprick sensibility was measured delivering stimuli with a BD™ 18 G Blunt Fill Needle.…”
Section: Methodsmentioning
confidence: 99%
“…Very often, prognostic statements are difficult to make because commonly used neurological and psychological test batteries are not feasible in pediatric patients after acquired hypoxic brain injury. To assess the progress of rehabilitation, Berger developed a vigilance score evaluated once a week by the whole rehabilitation team (20). He also found that improvements of the vigilance score were observed predominantly during the first 12 weeks after the insult, stressing the importance of early effective rehabilitation.…”
Section: Neurological Rehabilitationmentioning
confidence: 99%